Evaluation of a standardised assay for the measurement of antibodies to double-stranded (native) DNA. - Davis, P (1977)
A standardised commercially available radioimmunoassay kit for the detection of antibodies to native DNA (N-DNA) has been evaluated in clinical practice. This test system is shown to be a reliably reproducible method of detecting these antibodies. In addition, evaluation of the purity of the radiolabelled test antigen in this assay has shown it to be almost entirely double stranded (native) DNA with virtually no contamination with single stranded (denatured) DNA, and with few areas of single stranded breaks or ends in the duplex molecule. The inclusion of known standards and precise characterisation of the DNA has partially overcome variability in results and provides for interlaboratory standardisation which is lacking in the techniques used at present.